Virtual Currency Policy as Alternative Remittance Instrument: A Comparative Study of Indonesia and Philippines - Maulana, Muhammad Rois; Triarda, Reza (Journal of Transformative Governance and Social Justice, 2026)
In the contemporary digital economy, migrant remittances serve as a crucial economic stabilizer for Indonesia and the Philippines. However, conventional financial channels remain burdened by high transfer costs and procedural inefficiencies. Blockchain-based Virtual Currency (VC) introduces a potential solution through enhanced transaction speed, transparency, and affordability. Both states demonstrate distinctly different regulatory orientations toward VC utilization in remittances. This study employs a qualitative Most Similar Systems Design (MSSD) to compare policymaking in Indonesia and the Philippines by focusing on “Political Remittance”. Data derive from regulatory documents and academic sources. The Philippines demonstrates a progressive regulatory stance, informed by the institutionalized “Bagong Bayani” discourse and the significant macroeconomic weight of remittances. These conditions enhance diaspora political leverage, enabling coordinated advocacy and facilitating regulatory innovation alongside strong private-sector participation. In contrast, Indonesia’s lower remittance dependency sustains a protection-oriented regulatory paradigm grounded in the “Pahlawan Devisa” narrative, wherein financial experimentation is subordinated to risk mitigation. The relatively weak organizational infrastructure of Indonesian migrant advocacy further constrains policy reform. VC legalization emerges as a politically contingent process shaped by diaspora influence. The Philippines’ empowered transnational networks drive regulatory adaptation, while Indonesia’s limited migrant political agency reinforces conservatism in financial innovation.